Resin composition
The resin composition addresses high dielectric constants and low glass transition temperatures in copper foil substrates by combining specific resins and additives, ensuring low dielectric loss and high glass transition temperature for reliable high-frequency transmission.
Patent Information
- Application Number
- CN202310975016.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2023-08-04
- Publication Date
- 2024-12-31
Smart Images

Figure BDA0004376884700000021 
Figure BDA0004376884700000041 
Figure BDA0004376884700000081
Abstract
Description
Technical Field
[0001] The present invention relates to a composition, and in particular to a resin composition. Background Art
[0002] In recent years, with the development of 5G communications, the materials of copper foil substrates have been developed towards the goal of lower dielectric properties. The dielectric constant of the current copper foil substrate is about 3.2 to 5.0, which is not conducive to future high-frequency and fast transmission applications. At present, attempts have been made to add new low-dielectric resins such as polystyrene resins to the resin composition to reduce the loss factor of the copper foil substrate. However, the copper foil substrate prepared using such new low-dielectric resins reduces the glass transition temperature while reducing the loss factor.
[0003] Based on the above, developing a low dielectric resin composition with low dielectric constant, low dissipation factor and high glass transition temperature (Tg) is an urgent goal for those skilled in the art. Summary of the invention
[0004] The present invention provides a resin composition having low dielectric constant, low loss factor, high glass transition temperature and low bonding strength change rate.
[0005] The resin composition of the present invention comprises a resin mixture, which comprises a first resin polymerized from a monomer mixture comprising styrene, divinylbenzene and ethylene, a second resin comprising a polyphenylene ether resin modified by bismaleimide, a third resin block polymerized from a monomer mixture comprising styrene and butadiene, and acenaphthylene.
[0006] In one embodiment of the present invention, based on the total weight of the resin mixture, the content of the first resin is 10wt% to 40wt%, the content of the second resin is 30wt% to 50wt%, the content of the third resin is 10wt% to 30wt%, and the content of acenaphthylene is 10wt% to 30wt%.
[0007] In one embodiment of the present invention, the glass transition temperature of the resin composition is greater than 220°C.
[0008] In one embodiment of the present invention, the strength change rate of the resin composition after reliability testing is less than 10%.
[0009] In one embodiment of the present invention, the monomer mixture of the first resin includes 10 mol% to 40 mol% of styrene, 10 mol% to 40 mol% of divinylbenzene, and 10 mol% to 20 mol% of ethylene.
[0010] In one embodiment of the present invention, the number average molecular weight of the first resin is 4500 to 6500.
[0011] In one embodiment of the present invention, the second resin is represented by the following chemical formula:
[0012]
[0013] wherein R is a direct bond, a methylene group, an ethyl group, an isopropyl group, a 1-methylpropyl group, a sulfone group or a fluorenyl group, and n is an integer between 3 and 25.
[0014] In one embodiment of the present invention, the resin composition further comprises a siloxane coupling agent, wherein the amount of the siloxane coupling agent added is 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the resin mixture.
[0015] In one embodiment of the present invention, the resin composition further comprises a flame retardant, wherein the amount of the flame retardant added is 10 parts by weight to 50 parts by weight based on 100 parts by weight of the resin mixture.
[0016] In one embodiment of the present invention, the resin composition further comprises spherical silica, wherein the content of the spherical silica accounts for 30 wt % to 60 wt % of the total of the spherical silica, the flame retardant and the resin mixture.
[0017] Based on the above, since the resin composition of the present invention includes a first resin polymerized from a monomer mixture including styrene, divinylbenzene and ethylene, a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture including styrene and butadiene, and acenaphthylene, the substrate made of the resin composition can achieve the characteristics of low dielectric constant, low dissipation factor, high glass transition temperature and low adhesive strength change rate, thereby improving its reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] none DETAILED DESCRIPTION
[0019] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are illustrative only, and the present invention is not limited thereto.
[0020] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as the arbitrary value and the smaller numerical range are written in the description text of the specification.
[0021] The resin composition of one embodiment of the present invention includes a resin mixture, wherein the resin mixture includes a first resin polymerized from a monomer mixture including styrene, divinylbenzene and ethylene, a second resin including a polyphenylene ether resin modified by bismaleimide, a third resin block polymerized from a monomer mixture including styrene and butadiene, and acenaphthylene. In some embodiments, the resin composition also includes a flame retardant, spherical silica, a siloxane coupling agent and / or other additives. The various components described above will be described in detail below.
[0022] Resin mixture
[0023] In this embodiment, the resin mixture may include a first resin polymerized from a monomer mixture including styrene, divinylbenzene and ethylene, a second resin including a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture including styrene and butadiene, and acenaphthylene.
[0024] First Resin
[0025] In the present embodiment, the first resin may be polymerized from a monomer mixture including styrene, divinylbenzene and ethylene. In the monomer mixture, the molar ratio of styrene: divinylbenzene: ethylene may be 1:1:1 to 2:2:1. For example, the monomer mixture of the first resin includes 10 mol% to 40 mol% of styrene, 10 mol% to 40 mol% of divinylbenzene and 10 mol% to 20 mol% of ethylene. In some embodiments, the number average molecular weight of the first resin may be 4500 to 6500.
[0026] In some embodiments, the first resin may be present in an amount of 10 wt % to 40 wt % based on the total weight of the resin mixture. Adding the first resin to the resin composition may help reduce the dielectric constant of the resin composition.
[0027] Second resin
[0028] In this embodiment, the second resin may include a polyphenylene ether resin modified with bismaleimide. For example, the second resin of the present invention may be a polyphenylene ether resin modified with bismaleimide disclosed in Taiwan Patent Publication No. 1774559, the disclosure of which is incorporated herein by reference in its entirety.
[0029] For example, the chemical structure of the polyphenylene ether resin modified with bismaleimide can be represented by the following chemical formula:
[0030]
[0031] wherein R can be, for example, a direct bond, a methylene group, an ethyl group, an isopropyl group, a 1-methylpropyl group, a sulfone group or a fluorene group, and
[0032] n may be an integer between 3 and 25, preferably an integer between 10 and 18.
[0033] The polyphenylene oxide resin modified with bismaleimide can be formed by the manufacturing method disclosed in Taiwan Patent Publication No. 1774559, but the present invention is not limited thereto. The polyphenylene oxide resin modified with bismaleimide can also be formed by other suitable modification methods.
[0034] In some embodiments, the content of the second resin may be 30 wt % to 50 wt % based on the total weight of the resin mixture. Since the chemical structure of the second resin has both a main chain of polyphenylene ether and a terminal modified by a highly heat-resistant reactive group (i.e., bismaleimide), the second resin has a relatively low dielectric constant and dielectric loss.
[0035] The third resin
[0036] In the present embodiment, the third resin is formed by block polymerization of a monomer mixture including styrene and butadiene. The third resin is, for example, a styrene-butadiene-styrene block copolymer (SBS). In some embodiments, the third resin may be formed by polymerization of a monomer mixture including 5 mol% to 40 mol% styrene, 55 mol% to 90 mol% 1,2-butadiene, and 5 mol% to 30 mol% 1,4-butadiene. In some embodiments, the weight average molecular weight of the third resin may be 3500 to 5500.
[0037] In some embodiments, the third resin may be included in an amount of 10 wt % to 30 wt % based on the total weight of the resin mixture.
[0038] Acenaphthylene
[0039] Acenaphthylene is used as a crosslinking agent in the resin mixture. Due to its structural characteristics, it can improve the fluidity of the resin composition and increase the glass transition temperature. In some embodiments, the content of acenaphthylene can be 10wt% to 30wt% based on the total weight of the resin mixture. When the content of acenaphthylene is below 10wt%, the overall effect on the resin mixture is not significant; when the content of acenaphthylene is above 30wt%, the dielectric loss of the resin mixture will increase, which is not conducive to the application of the substrate for high-frequency transmission.
[0040] Flame retardant
[0041] In this embodiment, the flame retardant may be a phosphorus-containing flame retardant or a bromine-containing flame retardant. Specific examples of the flame retardant may include, but are not limited to, Exolit OP 935 (available from Clariant), SPB-100 (available from Otsuka Chemical), PX-200 (available from Daihachi Chemical), and PQ-60 (available from Shinichi Chemical).
[0042] In some embodiments, the flame retardant may be added in an amount of 10 parts by weight to 50 parts by weight based on 100 parts by weight of the resin mixture.
[0043] Spherical silica
[0044] In this embodiment, the spherical silica is preferably prepared by a synthetic method to reduce electrical properties and maintain fluidity and filling properties. The spherical silica may have a surface modification of acrylic or vinyl, a purity of about 99.0% or more, and an average particle size D50 of about 2.0 μm to 3.0 μm.
[0045] In some embodiments, the content of the spherical silica accounts for 30 wt % to 60 wt % of the total of the spherical silica, the flame retardant and the resin mixture.
[0046] Siloxane coupling agent
[0047] In this embodiment, the siloxane coupling agent may include but is not limited to siloxane compounds. In addition, according to the type of functional groups, it can be divided into amino silane compounds, epoxy silane compounds, vinyl silane compounds, ester silane compounds, hydroxyl silane compounds, isocyanate silane compounds, methacryloxy silane compounds and acryloxy silane compounds.
[0048] In some embodiments, the amount of the siloxane coupling agent added may be, for example, 0.1 to 5 parts by weight based on 100 parts by weight of the resin mixture. The siloxane coupling agent can enhance the compatibility and cross-linking degree of the resin composition with the glass fiber cloth and powder.
[0049] Other additives
[0050] In addition to the above components, the resin composition of the present invention may further include other additives, such as an initiator, a leveler, an antioxidant, etc. In some embodiments, the initiator may be a peroxide initiator.
[0051] In some embodiments, based on 100 parts by weight of the resin mixture, the content of the additive may be, for example, 0.1 parts by weight to 5 parts by weight, so as to achieve the function of the additive without affecting the overall dielectric properties and adhesion of the resin composition.
[0052] It should be noted that the resin composition of the present invention can be processed into a prepreg and / or a copper foil substrate (CCL) according to actual design requirements. Therefore, the prepreg and copper foil substrate made using the resin composition of the present invention also have low dielectric constant, low dissipation factor, high glass transition temperature and good bonding properties, and thus have better reliability. In more detail, the prepreg and copper foil substrate made of the resin composition may have a dielectric constant of about 3.0 to 3.1, a dissipation factor of about 0.0015 or less than 0.0015, and may have a glass transition temperature of more than 220 degrees, such as a glass transition temperature of about 220 degrees to about 270 degrees, and the reliability test bonding strength change rate is less than 10%, so as to flexibly adapt to environmental changes and improve reliability.
[0053] The resin composition of the present invention is described in detail below by means of experimental examples. However, the following experimental examples are not intended to limit the present invention.
[0054] Preparation Example: Preparation of the Second Resin
[0055] A low molecular weight polyphenylene ether resin material with a number average molecular weight (Mn) of less than or equal to 12,000 or less than or equal to 10,000 (for example, Mn = 500, 1400, 1600 or 1800) is dissolved in dimethylacetamide, followed by the addition of potassium carbonate and tetrafluoronitrobenzene. The above reaction solution is heated to 140°C and reacted for 8 hours, then cooled to room temperature, and then filtered to remove the solid. Methanol / water is used to precipitate the filtrate, and the precipitate is the nitrated polyphenylene ether resin. After the nitrated polyphenylene ether resin is dissolved in dimethylacetamide, it is hydrogenated at 90°C for 8 hours to obtain an aminated polyphenylene ether resin. The aminated polyphenylene ether resin is then placed in toluene, and maleic anhydride and p-toluenesulfonic acid are added thereto, and the temperature is raised to 120 degrees and refluxed, and the reaction is performed for 8 hours to obtain a second resin. It is a polyphenylene ether resin (PPE-BMI) modified with bismaleimide.
[0056] Examples 1-3 and Comparative Example 1
[0057] Examples 1-3 and Comparative Example 1 are varnishes (Varnish) of thermosetting resin compositions formed by mixing the resin compositions shown in Table 1 with toluene. The varnish is impregnated with Nan Ya fiberglass cloth (Nan Ya Plastics Corporation, cloth type 1078LD) at room temperature, and then dried at 170°C (impregnation machine) for several minutes to obtain a prepreg with a resin content of 79wt%. Finally, four prepregs are stacked layer by layer between two 35μm thick copper foils, and the temperature is maintained at a constant temperature for 20 minutes at a pressure of 25kg / cm2 and a temperature of 85°C. Then, the temperature is heated to 210°C at a heating rate of 3°C / min, and the temperature is maintained at a constant temperature for 120 minutes. Then, the prepreg is slowly cooled to 130°C to obtain a 0.59mm thick copper foil substrate.
[0058] In Table 1, the detailed information of each component is as follows:
[0059] First resin: purchased from Denka, model: LDM
[0060] Second resin: The second resin of the preparation example was used.
[0061] The third resin: purchased from Japan Soda Co., Ltd., model: 1,2-SBS Type-C
[0062] Acenaphthylene: purchased from JFE Chemical
[0063] Spherical silica: purchased from Sanshiki Company, model: EQ2410-SMC
[0064] Flame retardant: purchased from Jinyi Chemical Company, model: PQ-60
[0065] Siloxane coupling agent: purchased from Dow Corning, model: Z-6030
[0066] Initiator: purchased from ARKEMA, model: Luperox F
[0067] Evaluation Methodology
[0068] The copper foil substrates produced in each example and comparative example were evaluated according to the following method, and the results of the evaluation are described in Table 1.
[0069] The glass transition temperature (°C) was measured by dynamic mechanical analyzer (DMA).
[0070] Water absorption (%): After the sample is heated in a pressure cooker at 120°C and 2atm for 120 minutes, the weight change before and after heating is calculated.
[0071] Heat resistance: After heating the sample in a 120℃ and 2atm pressure cooker for 120 minutes, immerse it in a 288℃ soldering furnace and record the time required for the sample to delaminate. If the immersion time is greater than 10 minutes without delamination, it is evaluated as OK; if the immersion time is less than 10 minutes and delamination occurs, it is evaluated as unOK.
[0072] Reliability test-Peeling strength test:
[0073] The copper foil substrate (made of 4 prepregs pressed together) was cut into rectangular samples with a width of 30mm and a length greater than 50mm, and the surface copper foil was etched, leaving only a long strip of copper foil with a width of 3mm and a length greater than 50mm. The force required to initially pull the copper foil away from the surface of the substrate insulation layer (F1) and the force required to pull the copper foil away from the surface of the substrate insulation layer after 1000 hours in an environment of 85°C and 85% relative humidity (F2) were measured using a universal testing tensile machine. The strength change rate was then calculated as (F2-F1) / F1*100%.
[0074] Dielectric constant Dk: The dielectric constant Dk was measured at a frequency of 10 GHz using a dielectric analyzer (HP Agilent E4991A).
[0075] Dissipation factor Df: The dissipation factor Df at a frequency of 10 GHz was measured using a dielectric analyzer (HP Agilent E4991A).
[0076] Resin flow rate: Press at 170°C ± 2.8°C with 200 ± 25 PSI for 10 minutes. After melting and cooling, punch out the disc, weigh the disc accurately, and calculate the resin outflow.
[0077] Resin phase separation (section analysis):
[0078] Step 1: Cut the copper foil substrate into 1cm*1cm size and place it into the mold for resin grouting.
[0079] Step 2: After the resin is completely dried and hardened, grind and polish the sample.
[0080] Step 3: Use a high-resolution microscope such as OM / SEM to analyze the sample and confirm whether there is resin phase separation inside the sample.
[0081] Table 1
[0082]
[0083] As shown in Table 1, compared with Comparative Example 1 in which acenaphthylene is not added to the resin composition, Examples 1-3 in which acenaphthylene is included in the resin composition have a higher glass transition temperature and maintain low dielectric properties (such as low dielectric constant and low loss factor) at high frequencies. In addition, Examples 1-3 have better adhesion than Comparative Example 1 after 1000 hours in an environment of 85°C and 85% relative humidity. It can be seen that Examples 1-3 exhibit good reliability and are suitable for application in high-frequency transmission substrates.
[0084] In summary, since the resin composition of the present invention includes a first resin polymerized from a monomer mixture including styrene, divinylbenzene and ethylene, a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture including styrene and butadiene, and acenaphthylene, the substrate made from the resin composition can achieve the characteristics of low dielectric constant, low dissipation factor, high glass transition temperature and low adhesive strength change rate, thereby improving its reliability.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A resin composition, characterized in that: include: Resin mixture comprising: A first resin is polymerized from a monomer mixture including styrene, divinylbenzene and ethylene; The second resin includes a polyphenylene ether resin modified with bismaleimide; A third resin formed by block polymerization of a monomer mixture including styrene and butadiene; and Acenaphthylene.
2. The resin composition according to claim 1, characterized in that Based on the total weight of the resin mixture, the first resin is present in an amount of 10 wt % to 40 wt %, the second resin is present in an amount of 30 wt % to 50 wt %, the third resin is present in an amount of 10 wt % to 30 wt %, and acenaphthylene is present in an amount of 10 wt % to 30 wt %.
3. The resin composition according to claim 1, characterized in that The glass transition temperature of the resin composition is greater than 220°C.
4. The resin composition according to claim 1, characterized in that The reliability test of the resin composition shows that the strength change rate is less than 10%.
5. The resin composition according to claim 1, characterized in that The monomer mixture of the first resin includes 10 mol% to 40 mol% of styrene, 10 mol% to 40 mol% of divinylbenzene, and 10 mol% to 20 mol% of ethylene.
6. The resin composition according to claim 1, characterized in that The number average molecular weight of the first resin is 4,500 to 6,500.
7. The resin composition according to claim 1, characterized in that The second resin is represented by the following chemical formula: wherein R is a direct bond, a methylene group, an ethyl group, an isopropyl group, a 1-methylpropyl group, a sulfone group or a fluorenyl group, and n is an integer between 3 and 25.
8. The resin composition according to claim 1, characterized in that The invention also comprises a siloxane coupling agent, wherein the addition amount of the siloxane coupling agent is 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the resin mixture.
9. The resin composition according to claim 1, characterized in that The invention also comprises a flame retardant, wherein the flame retardant is added in an amount of 10 to 50 parts by weight based on 100 parts by weight of the resin mixture.
10. The resin composition according to claim 9, characterized in that Also included is spherical silica, wherein the content of the spherical silica accounts for 30 wt % to 60 wt % of the total of the spherical silica, the flame retardant and the resin mixture.
